Phonological and morphological features of Boyash language varieties in Eastern Slovakia - Rosenberg, Mátyás (Romano džaniben, 2022)
The text first summarises historical research related to the Boyash communities in Eastern Slovakia and points out that the existing information is limited and rudimentary. A separate section is devoted to the categorisations of Boyash people and a brief account of the migration history of the Slovakian Boyash. The then paper focuses on preliminary linguistic data obtained through the author’s dialectological fieldwork over the last decade. It presents the system of Slavic and Hungarian loanwords, examines phonological and morphological features in detail and compares them with other language varieties in Slovakia and Hungary. The paper offers a brief description of the linguistic reality of an ethnic group that is still largely unknown.